2017
DOI: 10.1016/j.jdiacomp.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of structured testing versus routine testing of blood glucose in diabetes self-management: A randomized controlled trial

Abstract: Aims:To compare the effects of structured and routine testing regimens used in self-monitoring of blood glucose (SMBG) on glycemic control and diabetes self-management in insulin-naïve type 2 diabetes patients. Methods:Sixty-two outpatients with insulin-naïve type 2 diabetes were randomly allocated into two less-frequent SMBG usage groups: a structured testing group (STG) and a routine testing group (RTG). Subjects in STG measured 7-points on SMBG for 3 consecutive days once every two months without daily test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Improvements in the control group reduced the size of the effect of the intervention in these studies. Similar outcomes were observed in other studies, which report conservative or weakened between-group differences due to improvements in the control group [ 6 , 11 , 14 , 21 ]. Therefore, solely the recruitment to a clinical trial, independent of the interventions, resulted in improvements in HbA1c [ 22 ].…”
Section: Introductionsupporting
confidence: 89%
“…Improvements in the control group reduced the size of the effect of the intervention in these studies. Similar outcomes were observed in other studies, which report conservative or weakened between-group differences due to improvements in the control group [ 6 , 11 , 14 , 21 ]. Therefore, solely the recruitment to a clinical trial, independent of the interventions, resulted in improvements in HbA1c [ 22 ].…”
Section: Introductionsupporting
confidence: 89%
“…In previous studies, structured SMBG was shown to be effective for glycaemic control in type 2 diabetes patients treated with insulin . In a clinical trial with type 2 diabetes patients without insulin treatment, structured SMBG reduced the HbA 1c level by 0.32% . Mannucci E et al performed a meta‐analysis of the effect of structured SMBG on type 2 diabetes patients without insulin treatment and found that structured SMBG effectively reduced the HbA 1c level .…”
Section: Discussionmentioning
confidence: 99%
“…11 In a clinical trial with type 2 diabetes patients without insulin treatment, structured SMBG reduced the HbA 1c level by 0.32%. 12 Mannucci E et al performed a meta-analysis of the effect of structured SMBG on type 2 diabetes The data are expressed as the mean ± SD or the median. Statistics for categorical variables are expressed as the number of patients (percentage of patients).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that the usefulness of SMBG is related to the response and management of the BG measurements by both the healthcare professional and the client (Benhalima & Mathieu, ; Nishimura et al., ; Parkin, Buskirk, Hinnen, & Axel‐Schweitzer, ). Diabetes Self‐Management Education‐Support (DSME‐S) is a complex intervention (Powers et al., ).…”
Section: Introductionmentioning
confidence: 99%